EU energy security in the gas sector evolving dynamics, policy dilemmas and prospects - Proedrou, Filippos (Ashgate, 2012)
This book fills an important gap in the literature on energy security in the gas sector in the European Union, shedding light on the state of EU energy security in the gas sector, its interdependence with external suppliers and the current gas strategy. The book concludes with policy recommendations, particularly in the light of tougher environmental regulation